Capital Punishment: Islamic Criminal Law Perspective - annisa annisa; Eka Putra; Muhammad Asla Fathi (Universitas Sumatera Utara, 2023)
This paper delves into the multifaceted dimensions of capital punishment within Islamic criminal law, examining its application and underlying objectives. The study revolves around two primary objects: the application of capital punishment and the objectives of implementing the death penalty. By exploring these dimensions, this paper seeks to elucidate the intricate interplay between justice, societal well-being, and legal philosophy within Islamic jurisprudence. The first object addresses the legal framework and ethical considerations surrounding the practice of capital punishment. Drawing from both retributive and consequentialist theories, the analysis illuminates the dual nature of Islamic jurisprudence in its pursuit of fairness and societal harmony. The second object investigates the objectives underpinning the death penalty's application. Rooted in the concepts of benefits (maslahah) and justice, Islamic legal thought underscores the balanced amalgamation of individual rights and collective welfare. In conclusion, this paper underscores the significance of collaborative efforts among legal scholars, policymakers, and communities to ensure a just and nuanced application of capital punishment. Through comprehensive engagement, Islamic societies can advance a holistic approach to punishment that aligns with the ethos of justice and societal well-being.